Knee-Spine Syndrome, a Common Presentation in Elderly Patients Who Are Candidate for Knee Arthroplasty: Educational Corner - Alireza Moharrami; Mohammad Mirahmadi Eraghi; Shahabaldin Beheshti Fard; Ali Asadifar; Ali Salehi; Sadulla Sharifpour; SM Javad Mortazavi (Journal of Orthopedic and Spine Trauma)
Low back pain (LBP) is a significant issue in both clinical and public health settings, resulting in high healthcare and social costs. While knee joint pain is more prevalent than hip joint pain, standing posture is influenced not only by spinal alignment but also by hip and knee joint alignment. The knee and spine are interconnected anatomically, and degenerative changes in one area could often cause discomfort in the entire axis, leading to what is known as "knee-spine syndrome". LBP is a common condition associated with knee pain and can significantly affect the results of total knee arthroplasty (TKA). Surgeons need to consider knee-spine syndrome before any surgical intervention in patients with knee or back pain and explain it to the patients before the surgery. Keywords: Low Back Pain; Knee; Spine; Syndrome; Patellofemoral Pain Syndrome